The origin of domestication genes in goats - Zheng, Z.; Wang, X.; Li, M.; Li, Y.; Yang, Z.; Pan, X.; Gong, M.; Zhang, Y.; Guo, Y.; Wang, Y.; Liu, J.; Cai, Y.; et al. (American Association for the Advancement of Science, 2020)
Goat domestication selection mainly focused on immune and neural genes and involved both standing and introgressed variation.